Fatores associados aos sintomas depressivos em idosos: estudo EpiFloripa - Borges, Lucelia Justino; Benedetti, Tania R Bertoldo; Xavier, Andre Junqueira; d'Orsi, Eleonora (Revista de Saúde Pública, 2013)
OBJECTIVE To estimate the prevalence and associated factors of depressive symptoms in the elderly. METHODS Cross-sectional population based epidemiological study (The EpiFloripa Elderly survey) was carried out in two stage clusters, census tracts and households, with1.656 elderly individuals in Florianópolis, SC. The prevalence of depressive symptoms (outcome) was obtained using Geriatric Depression Scale (GDS-15) and its associations with socio-demographic, health, behavioral and social variables were assessed. Crude and adjusted prevalence ratios (PR) with 95% confidence intervals were calculated using Poisson regression. RESULTS Depressive symptoms were observed in 23.9% of the elderly individuals (95%CI 21.84;26.01). In the final model, depressive symptoms were associated with: 5 to 8 years of schooling (PR = 1.50, 95%CI 1.08;2.08); one to four years of schooling (PR = 1.62, 95%CI 1.18;2.23) and no schooling (PR = 2.11, 95%CI 1.46;3.05); being in a worse financial condition than at the age of 50 (PR = 1.33, 95%CI 1.02;1.74); cognitive impairment (PR = 1.45, 95%CI 1.21;1.75); perceiving their health to be regular (PR = 1.95, 95%CI 1.47;2.60) or poor (PR = 2.64, 95%CI 1.82;3.83); functional dependence (PR =1.83, 95%CI 1.43;2.33) and chronic pain (PR = 1.35, 95%CI 1.10;1.67). Factors with protective effects were: being in the 70 to 79 year old age group (PR = 0.77, 95%CI 0.64;0.93); physical activity in leisure time (PR = 0.75, 95%CI 0.59;0.94); participation in social or religious groups (PR = 0.80, 95%CI 0.64;0.99) and having sexual relations (PR = 0.70, 95%CI 0.53;0.94). CONCLUSIONS : Adverse clinical situations, being socioeconomically disadvantaged and low social and sexual activity were associated with depressive symptoms in the elderly.